(untitled) (Research, Society and Development, 2024)
This study aimed to analyze and compare the impact of the establishment of the Secretariat of Sports over the course of the administration from 2021 to 2024, using the Cultural Development and Access Index (IDAC) as the primary evaluation indicator. The investigation employed a quantitative methodological design, divided into data collection from the administrations (from 2013 to 2020 and from 2021 to 2024), calculation of the absolute and relative IDAC of both, and statistical analysis for comparison. The data were subjected to a Kolmogorov-Smirnov normality test and Levene’s test for homogeneity of variances. An independent t-test was used to compare the values. The analyses were conducted using JASP 16.2 software, adopting a significance level (p<0.05). Comparing the data over four years, an increase in the number of sports facilities was observed, from 164 to 395, while the population served decreased from 1,537,704 to 1,488,920 inhabitants. The total relative IDAC increased from 47% to 57%, indicating a more equitable distribution of sports facilities across the six Political-Administrative Regions (RPAs) of the city. It was concluded that the creation of the Municipal Secretariat of Sports was significant in improving access to sports in Recife, especially in areas previously lacking in sports infrastructure.